Childhood Trauma and Maladaptive Personality of Incarcerated Individuals in Punjab Prisons; The Moderating Role of Peer Influence - Umm-e-Habiba*; Memoona Amir; Zuhaa Hassan (`, 2025)
Criminal activity is a persistent aspect of human civilization that cuts beyond national borders, cultural standards, and historical periods. The goal of the present investigation was to find out how peer influence can moderate the association between childhood trauma and maladaptive personality traits among incarcerated individuals. A randomly selected group of one hundred incarcerated individuals (criminal or guilt) participated in the research either in jails or prisons of Punjab. Data were collected on demographic information sheet, Childhood Trauma Questionnaire (Bernstein et al., 1998), Friends’ Delinquent Behavior scale (Elliot et al., 1989), Personality Inventory for DSM-5 (PID-5) (Krueger et al., 2013). Results of Pearson product moment correlation indicated that childhood trauma along with its dimensions physical abuse, sexual abuse and physical neglect had a positive relationship with maladaptive personality. Moderation was done through SPSS Process Macro Hayes and the results indicated that significant moderating effect of peer influence for physical abuse and sexual abuse in predicting negative affect. It also highlighted that significant moderating effect of peer influence for physical neglect in predicting antagonism. The moderating effect of peer influence for physical abuse, emotional abuse and sexual abuse in predicting disinhibition is also significant. It is concluded that physical abuse and sexual abuse leads to negative affect, physical, emotional and sexual abuse increase disinhibition while physical neglect is effective in increasing antagonism with incarcerated individuals who have peer influence. Keywords: Childhood Trauma, Peer Influence, Maladaptive Personality, Incarcerated Individuals